Reinventing Place-identity and Embracing New Economic Opportunities: Promoting Creative Economy of Sanur Through Public Participation - Nyoman Gede Maha Putra; Ida Bagus Gede Parama Putra (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2019)
Every place on the planet has unique characters that make it distinguishable from other sites. Place-identity is the term widely accepted to explain this phenomenon. It is argued that the place-identity could not only strengthen the sense of belonging of the locals to a place and improve social cohesion but, in the age of global tourism, it could also increase the attractiveness of the place to visitors. Therefore, it contains economic values if managed in a proper way. But places are transforming. The dynamics of contemporary activities where tradition is seen as outdated, new government system, new economic activities, and new actors and their roles challenge the stability of place-identity. Unfortunately, the transformation of a place may benefit some actors but may trouble other groups. Some places, however, maintain their place-identity for the social and economic values it holds. Collaboration among different actors in managing the transformation of such place could maintain the place-identity of a place which ensures its attractiveness to visitors, sustains its economic values amidst rapid changes. The collaboration confirms no one is left behind. The case study research conducted in Sanur showed that the sustained place-identity could economically benefit all actors.